2015
DOI: 10.1096/fj.15-273953
|View full text |Cite
|
Sign up to set email alerts
|

STAT‐3 contributes to pulmonary fibrosis through epithelial injury and fibroblast‐myofibroblast differentiation

Abstract: Lung fibrosis is the hallmark of the interstitial lung diseases. Alveolar epithelial cell (AEC) injury is akey step that contributes to a profibrotic microenvironment. Fibroblasts and myofibroblasts subsequently accumulate and deposit excessive extracellular matrix. In addition to TGF‐β, the IL‐6 family of cytokines, which signal through STAT‐3, may also contribute to lung fibrosis. In the current manuscript, the extent to which STAT‐3 inhibition decreases lung fibrosis is investigated. Phosphorylated STAT‐3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 67 publications
12
124
0
Order By: Relevance
“…Immunohistochemical analysis revealed that both SERPINE1 and α-SMA at the tumor-advancing front of OSCCs were significantly associated with extracapsular spread of cervical lymph nodes, a prognostic marker of OSCC outcome, and the combination of α-SMA/SERPINE1 positivity was significantly associated with poor survival of OSCC patients [41]. Interestingly, C-188-9, a STAT-3 inhibitor, decreased pulmonary fibrosis and resulted in inhibition of fibroblast-to-myofibroblast differentiation and TGF-β-induced expression of multiple genes including SERPINE1 [42]. Another protein that may support the protumoral effects of CAFs on oral cancer cells is STC2, which we found to be upregulated in the secretome of CAFs and in TGF-β1-treated NOFs.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis revealed that both SERPINE1 and α-SMA at the tumor-advancing front of OSCCs were significantly associated with extracapsular spread of cervical lymph nodes, a prognostic marker of OSCC outcome, and the combination of α-SMA/SERPINE1 positivity was significantly associated with poor survival of OSCC patients [41]. Interestingly, C-188-9, a STAT-3 inhibitor, decreased pulmonary fibrosis and resulted in inhibition of fibroblast-to-myofibroblast differentiation and TGF-β-induced expression of multiple genes including SERPINE1 [42]. Another protein that may support the protumoral effects of CAFs on oral cancer cells is STC2, which we found to be upregulated in the secretome of CAFs and in TGF-β1-treated NOFs.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is implicated in cell growth and carcinogenesis, while STAT6 is responsible for promoting a more allergic phenotype. TGF-β1 treatment of lung myofibroblasts has been shown to activate STAT3 and promote proliferation adjacent of epithelial damage 113 . Either STAT dysregulation would result in an abnormal phenotype and could result in increased proliferation or exacerbation of fibrosis or asthma 33 .…”
Section: Genetic Susceptibility To Pulmonary Fibrosismentioning
confidence: 99%
“…Recent data also indicate that STAT3 contributes to the development of lung fibrosis as a regulator of TGF-β transcriptional activity (18 and Ppl -/-mouse lung ( Figure 7A). After bleomycin, P-STAT3 was increased from D3 to D14 in Ppl +/+ lungs, whereas only a transient and mild increase on D3 was noted in Ppl -/-lungs ( Figure 7A).…”
Section: αB-crystallin Expression Was Altered In Pplmentioning
confidence: 80%
“…IHC experiments showed a delayed activation of Stat3 in AECs and less P-Stat3 in fibrotic areas in Ppl -/-mice. Stat3 activation has been implicated in the fibrotic lung in patients with IPF and in bleomycin-induced lung fibrosis in mice (18,43). Alterations in the inflammatory environment of the lung in Ppl -/-mice may have caused the decrease in STAT3 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation